Acute coronary syndrome in COVID-19 patients - M. G. Chashchin; A. Yu. Gorshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2021)
Acute coronary syndrome (ACS) is caused by an acute mismatch between myocardial oxygen demand and its supply. This mechanism is largely associated with the progression of coronary atherosclerosis in combination with an inflammatory response, hypoxemia, and blood procoagulation. Patients with the coronavirus disease 2019 (COVID-19), aggravated by cardiovascular diseases and comorbidities, are at high risk of ACS.Aim. To analyze the publications, which reflects the development of ACS in patients with COVID-19, its pathogenesis, and clinical course. Material and methods. Literature data were searched using Google Scholar, PubMed, ScienceDirect, and Cyberleninka services. The analysis included data from clinical guidelines on COVID-19, data from clinical studies, reports, and systematic reviews.Results. This literature review summarizes and systematizes the data presented in modern publications, highlights the aspects of the clinical course and pathogenetic mechanisms underlying ACS in patients with COVID-19.Conclusion. The pathogenesis of COVID-19 is inextricably associated with the widespread cytopathic effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), uncontrolled immune response that causes systemic inflammation, as well as the coagulation system activation. In patients with COVID-19, along with the atherosclerosis, these mechanisms significantly increase the risk of ACS and can worsen its in-hospital course.